(untitled) (The Journal of Interdisciplinary Human Studies, 2026)
The article analyzes the impact of radicalization and violent extremism on human well-being and sustainable development. The research was carried out on the basis of reports of international organizations and scientific sources. The results show that radicalization intensifies under conditions of social inequality, limited economic opportunities, and political marginalization. Effective mechanisms for its prevention are also considered.